The August trials : the Holocaust and postwar justice in Poland - Kornbluth, Andrew, 1982- (Harvard University Press, 2021)
"When six years of resistance to Nazi occupation came to an end in 1945, a devastated Poland could agree with its new, Soviet-imposed rulers on little else beyond the need to punish German war criminals and their collaborators. But as the process of postwar retribution began to unearth evidence of enthusiastic local participation in the Holocaust, the hated government, traumatized populace, and fiercely independent judiciary found themselves struggling to salvage a sanitized vision of the past that could serve as the basis for national unity. Long dismissed as Stalinist farce, Poland's 32,000 trials for collaboration were in fact a scrupulous, complex search for the truth. Making use of unpublished memoirs, interviews, ministerial archives, and hundreds of individual case files, The August Trials documents how trials became the crucible in which the communist state and an unyielding society hammered out the foundational myth of modern Poland"--